Hepatoprotective Effects of Different Extracts From Triphala Against CCl4-Induced Acute Liver Injury in Mice - Xichuan Wei; Chuanhong Luo; Yanan He; Haozhou Huang; Fei Ran; Wei Liao; Peng Tan; Sanhu Fan; Yuan Cheng; Dingkun Zhang; Junzhi Lin; Li Han (Frontiers Media S.A., 2021)
Background:Triphala is a traditional polyherbal formula used in Indian Ayurvedic and Chinese Tibetan medicine. A wide range of biological activities have been attributed to Triphala, but the impact of various extraction methods on efficacy has not been determined.Purpose: The study aimed to evaluate Triphala extracts obtained by various methods for their hepatoprotective effects and molecular mechanisms in a mouse model of carbon tetrachloride (CCl4)-induced liver injury.Methods: HPLC fingerprinting was used to characterize the chemical characteristics of Triphala extracts obtained by (a) 0.5 h ultrasonication, (b) 2 h reflux, and (c) 4 h reflux. Hepatoprotective efficacy was evaluated in a mouse model of CCl4-induced liver damage. Serum levels of alanine transaminase (ALT) and aspartate aminotransferase (AST) were measured, as well as the liver antioxidant and inflammatory markers malondialdehyde superoxide dismutase glutathione peroxidase (GSH-Px), TNF-α, and IL-6. Gene and protein expression of Nrf-2 signaling components Nrf-2, heme oxygenase (HO-1), and NADPH Quinone oxidoreductase (NQO-1) in liver tissue were evaluated by real-time PCR and western blotting.Results: Chemical analysis showed a clear difference in content between extracts produced by ultrasonic and reflux methods. The pharmacological analysis showed that all three Triphala extracts reduced ALT, AST, MDA, TNF-α, and IL-6 levels and increased SOD and GSH-Px. Triphala extracts also induced transcript and protein expression of Nrf-2, HO-1, and NQO-1.Conclusion: Triphala extract prevents CCl4-induced acute liver injury. The ultrasonic extract of Triphala was most effective, suggesting that hepatoprotection may be related to the larger tannins via activation of Nrf-2 signaling.